Signaling System Renovation Plan for Suzhou Rail Transit Line 3 and Line 11 Through Train Operation - SUN Yao; LI Xin; SHEN Bingnai (Chengshi guidao jiaotong yanjiu)
Objective To facilitate the integration of passenger flow between Suzhou and Shanghai, Suzhou Rail Transit Line 3 and Line 11 are connected at Weiting Station, where passengers currently transfer via the concourse within the fare-paid zone, resulting in a restriction of the operational capacity for both Line 3 and Line 11. To meet the urgent need for capacity enhancement, a renovation plan of the signaling system for Line 3 and Line 11 through train operation is required. Method The existing conditions and technical differences between the signaling systems of Line 3 and Line 11 are analyzed. Based on different wireless communication standards, a signaling system renovation plan is proposed to meet the requirements of the through train operation between two lines. The implementation plan for the signaling system renovation is designed according to the project preparation schedule for Line 3 and Line 11 signaling system upgrade, focusing on modifications of the on-board signaling subsystem, ATS (automatic train supervision) subsystem, mainline station signaling subsystem, and depot signaling subsystem. Result & Conclusion Through adaptive modifications to the signaling systems of Line 3 and Line 11, train cross-line driverless operation is achieved, the compatibility and interchangeability of on-board ATC (automatic train control) equipment, ATS servers, and workstation hardware are implemented, allowing for uninterrupted automatic switching of vehicle-wayside wireless communication. Trains can operate seamlessly across Line 3 and Line 11 in FAO (fully automatic operation) mode, enhancing the operational efficiency of urban rail transit and improving the passenger travel experience.